Editorial for "Qualitative and Quantitative Reporting of a Unique Biparametric MRI: Towards Biparametric MRI‐Based Nomograms for Prediction of Prostate Biopsy Outcome in Men With a Clinical Suspicion of Prostate Cancer (IMPROD and MULTI‐IMPROD Trials)". Issue 5 (1st November 2019) - Hausmann, Daniel; Zoellner, Frank Gerrit; Kubik‐Huch, Rahel A.
Abstract : Level of Evidence: 5 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2020;51:1568–1569.